Effect of Zinc Supplementation on Serum Bilirubin Level in Term Neonates Undergoing Phototherapy - Mahmoud Eldesoky Ibrahim Eldesoky (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Neonatal jaundice is considered a major health problem in neonates owing to bilirubin deposition. Recently, zinc demonstrated a high efficiency in reduction of low bilirubin level when administrated in association with phototherapy. Aim of the work: To assess efficiency and safety of oral zinc as a therapy in treatment of indirect hyperbilirubinemia in term neonates during phototherapy. Patients and Methods:A total of 100 term neonates with indirect hyperbilirubinemia were divided into two equal groups: Intervention Group (n=50) received oral zinc sulphate preparation, in a dose of 5 mg twice daily in combination with phototherapy. Control group (n=50) received phototherapy without oral zinc supplementation. In both groups, the total serum bilirubin levels were measured at admission, 12 hours, 24 hours and at discharge. Results: Treatment of full-term neonates with hyperbilirubinemia by oral zinc sulfate at a dose of 5 mg given twice-daily induce a significant reduction of  total serum bilirubin [TSB] after 12 hours, 24 hours and at discharge when compared to the control group. The duration of phototherapy in intervention group was markedly decreased with statistically significant difference in comparison to the control group. However, there was no significant differences between groups regarding adverse effects of phototherapy and zinc therapy. Conclusion: Oral zinc could play a major role in the management of neonatal jaundice when administrated at dose of ten mg/day as it can decrease the neonatal TSB with subsequent reduction of phototherapy duration.